An arithmetic sequence
![a_1,a_2,a_3,\ldots,a_n,\ldots](https://tex.z-dn.net/?f=a_1%2Ca_2%2Ca_3%2C%5Cldots%2Ca_n%2C%5Cldots)
is one in which consecutive terms of the sequence differ by a fixed number, call it <em>d</em>. This means that, given the first term
, we can build the sequence by simply adding <em>d</em> :
![a_2=a_1+d](https://tex.z-dn.net/?f=a_2%3Da_1%2Bd)
![a_3=a_2+d](https://tex.z-dn.net/?f=a_3%3Da_2%2Bd)
![a_4=a_3+d](https://tex.z-dn.net/?f=a_4%3Da_3%2Bd)
and so on, the general pattern governed by the recursive rule,
![a_n=a_{n-1}+d](https://tex.z-dn.net/?f=a_n%3Da_%7Bn-1%7D%2Bd)
We can exploit this rule in order to write any term of the sequence in terms of the first one. For example,
![a_3=a_2+d=(a_1+d)+d=a_1+2d](https://tex.z-dn.net/?f=a_3%3Da_2%2Bd%3D%28a_1%2Bd%29%2Bd%3Da_1%2B2d)
![a_4=a_3+d=(a_1+2d)+d=a_1+3d](https://tex.z-dn.net/?f=a_4%3Da_3%2Bd%3D%28a_1%2B2d%29%2Bd%3Da_1%2B3d)
and so on up to
![a_n=a_1+(n-1)d](https://tex.z-dn.net/?f=a_n%3Da_1%2B%28n-1%29d)
In this case, we're not given the first term right away, but the 17th. But this isn't a problem; we can use the same exploit to get
![a_{18}=a_{17}+d](https://tex.z-dn.net/?f=a_%7B18%7D%3Da_%7B17%7D%2Bd)
![a_{19}=a_{17}+2d](https://tex.z-dn.net/?f=a_%7B19%7D%3Da_%7B17%7D%2B2d)
![a_{20}=a_{17}+3d](https://tex.z-dn.net/?f=a_%7B20%7D%3Da_%7B17%7D%2B3d)
and so on, up to the next term we know,
![a_{28}=a_{17}+11d=-40+11d](https://tex.z-dn.net/?f=a_%7B28%7D%3Da_%7B17%7D%2B11d%3D-40%2B11d)
(Notice how the subscript of <em>a</em> on the right and the coefficient of <em>d</em> add up to the subscript of <em>a</em> on the left.)
The 28th term is -73, so we can solve for <em>d</em> :
![-73=-40+11d\implies -33=11d\implies d=-3](https://tex.z-dn.net/?f=-73%3D-40%2B11d%5Cimplies%20-33%3D11d%5Cimplies%20d%3D-3)
To get the first term of the sequence, we use the rule found above and either of the known values of the sequence. For instance,
![a_{17}=a_1+16d\implies-40=a_1-16\cdot3\implies a_1=8](https://tex.z-dn.net/?f=a_%7B17%7D%3Da_1%2B16d%5Cimplies-40%3Da_1-16%5Ccdot3%5Cimplies%20a_1%3D8)
Then the recursive rule for this particular sequence is
![\begin{cases}a_1=8\\a_n=a_{n-1}-3&\text{for }n>1\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Da_1%3D8%5C%5Ca_n%3Da_%7Bn-1%7D-3%26%5Ctext%7Bfor%20%7Dn%3E1%5Cend%7Bcases%7D)